Demographics and Halal food consumption: a quantitative analysis - Md Sawari, Siti Salwa; Abd Rahman, Nur Hidayah; Rasool, Shahid; Paramboor, Jaafar (Academic Inspired Network, 2019)
The objective of this paper is to examine the demographic differences in halal food consumption. Data collected from 730 respondents in Peninsular Malaysia. All respondents were required to answer survey questionnaires related to their demographics and attitude towards halal food. The result of this study shows that the majority of Muslims in Malaysia have high-level awareness in consuming halal food. For demographic characteristics focusing on the gender, a significant difference was found (p < 0.05). This research also identified that there was no significant difference in respondents’ attitude towards halal food consumption based on age and origin region (p > 0.05). The practical implication is specifically for the halal food industry as they would be able to promote the halal culture referring to the findings of this particular study.